Sarah Ann Edwards, (1865–1947): Baptist Social Reformer and Suffragist - Smith, Karen E. (Baptist quarterly, 2026)
Over the last decade there has been renewed interest in women's history in England and Wales. However, while the names of some women as suffragists, poets, athletes, and singers may now be known, only limited attention has been given to Welsh Nonconformist women and their significant contribution both to chapel life and to other social and civic work. This presentation highlights the story of Sarah Ann (Evans) Edwards (1865–1947), a Baptist Social Reformer and Suffragist, who worked tirelessly for the rights of women in England and Wales.